Pengolahan Citra Huruf Hijaiyah Menggunakan Algoritma Support Vector Machine - Lisa Amelia Putri; Andriani Sitorus; Nurul Fitriah; Havni Virul; Syawaliah Putri Rangkuti; Supiyandi Supiyandi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Hijaiyah letters are the alphabet used in Arabic and the Koran. Automatic recognition of hijaiyah letters has many benefits, especially in the fields of education and learning Arabic and the Koran. This research aims to classify hijaiyah letter recognition using image processing techniques and the Support Vector Machine (SVM) algorithm. We collected a dataset of images of 5 hijaiyah letters with a total of 400 images obtained from Google and also Iqro'. The train:test ratio is 8:2. Experimental results show that the proposed approach can achieve high accuracy in recognizing hijaiyah letters with an accuracy rate of 99.16%.